Who Runs? Honesty and Self-Selection into Politics - Sebastian Fehrler; Urs Fischbacher; Maik T. Schneider (Institute for the Study of Labor (IZA), 2016)
We examine the incentives to self-select into politics and how they depend on the transparency of the entry process. To this end, we set up a two-stage political competition model and test its key mechanisms in the lab. At the entry stage, potential candidates compete in a contest to become their party's nominee. At the election stage, the nominated candidates campaign by making non-binding promises to voters. Confirming the model's key predictions, we find in the experiment that dishonest people over-proportionally self-select into the political race; and that this adverse selection effect can be prevented if the entry stage is made transparent to voters.
Keywords: C92; D71; D83; 330; candidates; elections; campaigns; primaries; contest; voting; political economy; experiment; lying aversion; self-selection; cheap talk